Visual Representations of Dance and Gender in the Hebrew Bible and the Ancient World - Rashkow, Ilona (Postscripts: The Journal of Sacred Texts, Cultural Histories, and Contemporary Contexts, 2025)
This essay outlines the visual reception of dance in the Hebrew Bible and the broader ancient world. It begins with depictions of dance within the visual culture of the ancient Near East, as well as Greek, Roman and Egyptian visual art. It next explores texts from the Hebrew Bible which depict dance and outlines various ways in which these have been brought to life visually through the centuries. The representation of gender in these visual depictions is drawn out and explored throughout the essay.